Dari Tatap Muka ke Tatap Layar: Transformasi Interaksi Sosial Remaja di Era Digital - Hukunala, Glen; Nahuway, Johana (Universitas Pattimura, 2024)
This article explores the transformation of adolescent social interaction patterns in the digital era, focusing on social media users in Liang Village, a rural community. This study is grounded in the growing phenomenon of a shift from face-to-face interaction to screen-mediated communication, a hallmark of contemporary digital culture. Employing a qualitative descriptive approach with a case study design, this research involved six adolescents aged 14–18 and two parents as key informants. Data were collected through in-depth interviews and participant observation to capture the nuanced dynamics of social interaction. The findings reveal that social media has reshaped the way adolescents connect, replacing meaningful face-to-face interactions with more superficial and instant digital engagements. The study also identifies a rising tendency toward social anxiety and a decline in adolescents’ ability to build authentic interpersonal relationships. While social media facilitates the maintenance of existing connections, its overall impact on the quality and quantity of social relationships appears to be largely detrimental. The novelty of this study lies in its rural context, which remains underrepresented in social media research. This article recommends adaptive educational and cultural interventions to strengthen adolescents' capacity to foster healthy social relationships. The study contributes to digital sociology and opens new avenues for discourse in social sciences and humanities, particularly regarding technology's impact on marginalized communities.